Feasibility and accuracy of cord blood sampling for admission laboratory investigations: A pilot trial. (10th November 2020) - Medeiros, Poliana De B; Stark, Michael; Long, Miriam; Allen, Elizabeth; Grace, Erin; Andersen, Chad
Abstract : Aim: Phlebotomy losses greatly contribute to anaemia following preterm birth. Therefore, the possibility of drawing initial tests from the placenta seems attractive. There is a lack of literature regarding the feasibility and accuracy of pathology tests taken from umbilical arterial and venous (UAB/UVB) compared to blood collected from the newborn. Methods: UAB and UVB complete blood pictures were compared with the initial neonatal blood test. The relationship between UAB, UVB and neonatal complete blood picture values was determined by Spearman's Rho correlation with absolute values compared by Kruskal‐Wallis. P < 0.05 was considered significant. Results: Neonatal haemoglobin, white cell count, immature/total ratio and platelets were significantly correlated to the corresponding values in the UAB and UVB (all P < 0.001). While UAB and UVB haemoglobin and white cell count were similar, both were significantly lower than the neonatal values ( P < 0.001 and P = 0.014, respectively). No difference was seen for immature/total ratio and platelet concentrations. UVB blood culture (BC) was feasible (90%), even with delayed cord clamping, and the UVB BC volume was significantly higher ( P < 0.001), with a low rate of BC contamination (1.5%). Conclusions: Our findings support the feasibility and accuracy of umbilical blood in place of blood collected from the newborn. This reduces the phlebotomy losses and allows higher blood volume collection which may increase the sensitivity of BC collection.